ALGORITHMIZATION AND PROGRAMMING - Tsyganova, A.D.; Danilova, V.V. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The manual is written in accordance with the requirements of the State Program for the Development of Education and Science of the Republic of Kazakhstan for 2016-2019 - a phased transition of the formation of the Republic of Kazakhstan to a trilingual education and is intended for students of polyglot groups of specialty 5B011100 "Informatics". This manual is a guide to mastering the skills of developing and implementing algorithms for solving problems in the programming environment in English. At the beginning of each topic, the manual contains the necessary theoretical material; an analysis of the solution of demonstration examples is conducted, the methodology for developing algorithms for solving these examples accompanied by the listing of ready-made programs or basic program fragments, is considered; made a selection of interesting practical tasks for the independent decision on each topic in the required volume given guidance, methodological recommendations for solving tasks. Particular attention is paid to the topics: procedural-modular programming technology, input-output data files, algorithms on graphs.